Analisa Kinerja Layanan Internet Pada SMK Muhammadiyah 3 Terpadu Pekanbaru Menggunakan Metode Quality of Service - Rendi Aulia Rahman; Iwan Iskandar; Muhammad Irsyad; Reski Mai Candra (STMIK Pringsewu, 2023)
The internet is a network that is used to connect computer devices to each other without being limited by the number users. The development the internet can be used for various means, one which is education. One of the schools that use the internet is SMK Muhammadiyah 3 Terpadu Pekanbaru. The school has a bandwidth speed of 300 Mbps originating from IndiHome and Dashnet. This study aims obtain information about the quality and existing internet services that this research hopes can be used as a reference by the administrators the internet network in schools. This study uses QoS (Quality of Service) parameters such as Delay, Jitter, Throughput, and Packet Loss. In addition, this study uses a software called wireshark. Wireshark functions to analyze data packets and quality on an internet network. The results this study get the index values of several QoS parameters. Based on the research, an index of 4 or in the very good category was obtained in terms of Delay, Jitter, Throughput, and Packet Loss both during busy and quiet hours. What's more, the school takes more advantage of the amount bandwidth available from IndiHome providers so they can drain school costs in procuring the network.